The Perpetrator-Victim Relationship: An Important Clue in Understanding Intimate Partner Homicide in China - Zhao, Shuhong (Journal of interpersonal violence, 2022)
Intimate partner homicide (IPH) is a global public health issue that has serious consequences for an individual?s health. Whereas prior research has made some progress analyzing the perpetrator-victim relationship in understanding the dynamics of IPH, research set in the context of China in this field using the perpetrator-victim relationship as a focal variable in analyzing IPH is still lacking. The current study addresses this gap and builds on existing research by exploring the significance of the perpetrator-victim relationship in order to facilitate a deeper understanding of IPH in China. After examining 979 IPH criminal judgments, the findings revealed that the perpetrator-victim relationship is an important clue in understanding IPH in China today. By analyzing the correlation between intimate relationships as a focal variable and other variables such as IPH characteristics and risk factors, it is possible to understand the prevalence of IPH in China in greater detail. Irrespective of the kind of relationship between the perpetrator and victim, the findings revealed that most of them come from lower socioeconomic backgrounds, have no previous history of intimate partner violence, and are not satisfied with their marriages. Although research has provided detailed explanations, the perpetrator-victim relationship remains neglected, especially in the context of research on contemporary China. The findings showed that over half of the perpetrators and victims had intimate relationships with people outside their marriages. This may be the main reason for the rapid increase in the number of instances of IPH, which seems to be in tandem with China?s rapid modernization and urbanization.